“Isn’t That Life, in a Way: Trying to Accommodate Dissonance?” Reflections on Lesbianism and the Life and Music of Ann Southam - Bernstein, Tamara (Circuit)

(untitled) (Circuit, musiques contemporaines, 2021)
Canadian composer Ann Southam (1937–2010) was a proud, outspoken, and generous feminist who found affinities between feminism and the minimalist musical language she developed in the late 1970s. At the same time, Southam was a very private person; it was only towards the end of her life that she began to speak on record about being gay. Music writer Tamara Bernstein, a friend of the composer, weighs the merits of focussing on this side of Southam’s life: the willingness with which Southam spoke in her final interviews about the difficulty of coming of age as a lesbian in the 1950s, and the fact that material related to this from her final interview has not been published until now; the importance of remembering how recently lgbtq rights were fully enshrined in Canadian law. Finally, alongside a caveat about the dangers of reductivism, and reminders that Southam found musical inspiration in other sources (e.g., nature), the author suggests ways in which Southam’s struggles with a sexual identity considered “dissonant” may have found their way into her music.